Electronic Components
By optimizing the orientation of the plating film made from a metal with a face-centered cubic structure in electronic components, the peeling issue is addressed, enhancing adhesion and ensuring operational reliability.
Patent Information
- Application Number
- JP2023545156
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-31
- Filing Date
- 2022-07-22
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2042-07-22
AI Technical Summary
In electronic components with external electrodes featuring a resin layer and a plating film, the plating film often peels off, leading to contact defects and operational issues.
The plating film is made of a metal with a face-centered cubic structure, and its orientation is optimized to achieve an F value of 0.20 or more and 0.50 or less, enhancing the adhesion between the resin layer and the plating film.
This approach effectively suppresses the peeling of the plating film, improves the adhesion between the resin layer and the plating film, and reduces internal breakdown, ensuring the electronic components operate normally.
Smart Images

Figure 0007663126000002 
Figure 0007663126000003 
Figure 0007663126000001
Abstract
Description
[Technical field]
[0001] The present invention relates to electronic components. [Background technology]
[0002] Electronic components such as positive temperature coefficient thermistors generally have external electrodes formed by laminating a conductive layer provided on the end of a ceramic body and a metal plating film formed by electrolytic plating, electroless plating, or the like. The plating film can be formed in one layer or multiple layers. In one example of a two-layer plating film, the first plating film in contact with the conductive layer is a nickel plating film for the purpose of improving heat resistance, and the second plating film covering the first plating film is a tin plating film for the purpose of improving solderability.
[0003] However, after mounting, electronic components may crack in the ceramic body due to impact, thermal stress, etc. To prevent this, Patent Document 1 proposes providing a conductive epoxy thermosetting resin layer (hereinafter sometimes referred to as "resin layer") containing metal powder between the baked electrode and the plating layer in the external electrode of the electronic component. The resin layer functions as a stress absorbing layer and can suppress the occurrence of cracks in the ceramic body. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-162771 Summary of the Invention [Problem to be solved by the invention]
[0005] In the case of external electrodes including a resin layer as in Patent Document 1, the plating film formed on the resin layer sometimes peels off. When the plating film peels off, poor contact occurs inside the external electrode, and there is a risk that the electronic component will not function properly. Patent Document 1 does not consider peeling of the plating layer formed on the resin layer.
[0006] The present invention has been made in light of the above circumstances, and has an object to suppress peeling of a plating film in an electronic component that has external electrodes having a plating film on a resin layer. [Means for solving the problem]
[0007] According to one aspect of the present invention, An electronic component comprising a ceramic body and external electrodes on ends of the ceramic body, the external electrode includes a resin layer containing a conductive powder and a plating film on and in direct contact with the resin layer, The plating film is made of a metal having a face-centered cubic structure, The electronic component has a plating film having a value of F, calculated by the following formula (1), of 0.20 or more and 0.50 or less. F = (P - P0) / (1 - P0) (1) In formula (1), P0 and P are calculated by the following formulas (2) and (3). P0=I0(111) / {I0(111)+I0(200)+I0(220)}...(2) P=I(111) / {I(111)+I(200)+I(220)}...(3) In formula (2), I0(111), I0(200), and I0(220) are the diffraction intensities of the (111), (200), and (220) planes, respectively, obtained from known powder X-ray diffraction data for the metal constituting the plating film; In formula (3), I(111), I(200) and I(220) are the diffraction intensities of the (111), (200) and (220) planes, respectively, obtained from the X-ray diffraction pattern of the plating film. Effect of the Invention
[0008] According to the present invention, peeling of the plating film formed on the resin layer can be suppressed. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an electronic component according to a first embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an electronic component according to a second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present inventors have conducted extensive research into preventing peeling of a plating film in an electronic component having an external electrode including a resin layer and a plating film in direct contact with the resin layer, and have found that peeling of the plating film can be prevented by improving the orientation of the metal material that constitutes the plating film, thereby completing the present invention. The reason why such an effect is obtained is unclear, but it is presumed to be due to the following mechanism.
[0011] In the rotating barrel method, which is a common plating method in the manufacture of electronic components, the plating film is formed while the surface of the plating film is smoothed (flattened) by the impact force caused by rotation. In this process, the plating film grows disorderly due to the flattening, resulting in a plating film with no uniform crystal orientation (i.e., no consistent crystallographic alignment). Furthermore, the plating film grows disorderly, which can cause defects in the metal bonds inside the plating film. In the case of such a plating film, the adhesion at the interface between the resin layer and the plating film is low, and furthermore, the strength of the plating film itself is low, so it is thought that the plating film will easily peel off at the interface between the resin layer and the plating film, or due to internal destruction of the plating film itself.
[0012] Therefore, the inventors of the present invention conducted further studies, believing that the crystallographic consistency of the plating film, and furthermore, the crystallographic consistency between the plating film and the conductive powder in the resin layer, contribute to the suppression of peeling of the plating film. As a result, the inventors of the present invention optimized the plating bath and plating conditions, and grew the plating film so that it was strongly oriented in a specific plane (the (111) plane), forming a plating film with a regular crystal structure. It is believed that such a plating film improves the adhesion between the resin layer and the plating film, and also improves the strength of the plating film itself, thereby suppressing peeling of the plating film.
[0013] Hereinafter, electronic components according to embodiments of the present invention will be described with reference to the drawings.
[0014] [Embodiment 1] Fig. 1 is a schematic cross-sectional view of an electronic component 10A according to a first embodiment of the present invention. An example of the electronic component 10A shown in Fig. 1 is a positive temperature coefficient (or positive temperature coefficient, PTC) thermistor. The electronic component 10A includes a ceramic body 20A and external electrodes provided on ends of the ceramic body 20A.
[0015] The electronic component 10A has at least one external electrode. The positive temperature coefficient thermistor shown in Fig. 1 has a pair of external electrodes 30, 40 provided on both ends of the ceramic body 20A. The external electrodes 30, 40 include at least a resin layer 32, 42 containing conductive powder, and a plating film 33, 43 in direct contact with the resin layer 32, 42. The external electrodes 30, 40 may further include a base layer 31, 41 provided between the end face 21A, 22A of the ceramic body 20A and the resin layer 32, 42, and a second plating film 34, 44 covering the plating film 33, 43.
[0016] As a result of intensive research, the present inventors have found that in order to suppress peeling of the plating films 33, 43 formed on the resin layers 32, 42, it is effective to form the plating films 33, 43 from a metal having a face-centered cubic structure and to preferentially orient the (111) plane as the orientation of the crystal structure of the plating films 33, 43. The value of F defined by the following formula (1) serves as an index for the orientation of the (111) plane of the plating films 33, 43. When the value of F obtained for the plating films 33, 43 is 0.20 or more and 0.50 or less, the adhesion between the resin layers 32, 42 and the plating films 33, 43 increases and internal destruction of the plating films 33, 43 is less likely to occur, which is believed to suppress peeling of the plating films 33, 43.
[0017] F = (P - P0) / (1 - P0) (1) In formula (1), P0 and P are calculated by the following formulas (2) and (3). P0=I0(111) / {I0(111)+I0(200)+I0(220)}...(2) P=I(111) / {I(111)+I(200)+I(220)}...(3) In formula (2), I0(111), I0(200), and I0(220) are the diffraction intensities of the (111), (200), and (220) planes, respectively, obtained from known powder X-ray diffraction data for the metal constituting the plating film; In formula (3), I(111), I(200) and I(220) are the diffraction intensities of the (111), (200) and (220) planes, respectively, obtained from the X-ray diffraction pattern of the plating film.
[0018] Known powder X-ray diffraction data for I0(111), I0(200) and I0(220) are available from the ICDD database.
[0019] I(111), I(200) and I(220) are determined from the diffraction patterns obtained by measuring the plating films 33 and 43 with an XRD diffractometer. A two-dimensional X-ray diffraction image obtained using a two-dimensional detector is converted into a one-dimensional profile, and the diffraction intensity value of the peak of each orientation plane is determined using the obtained one-dimensional profile. The diffraction intensity value is determined as a relative intensity with the maximum intensity set to 100.
[0020] As the XRD diffraction device, a micro X-ray diffraction device can be used. A specific example of the device is the D8 DISCOVER manufactured by BRUKER axs. Since it is necessary to perform XRD diffraction measurement of the plating films 33, 43 of the electronic component 10A, if the plating films 33, 43 are covered with the second plating films 34, 44, the second plating films 34, 44 are removed to expose the plating films 33, 43, and then the XRD diffraction of the plating films 33, 43 is measured. The second plating films 34, 44 can be removed, for example, by dissolving and removing the second plating films 34, 44 with a solvent that selectively dissolves only the second plating films 34, 44.
[0021] The value of F obtained from formulas (1) to (3) is an index of the orientation of the (111) plane of the material constituting the plating films 33 and 43. Formulas (1) to (3) will be described in detail below.
[0022] The Lotgering factor f is known as a measure of the degree of orientation of a given orientation plane. The Lotgering factor f is calculated by the following formula (4) using the intensity of X-rays diffracted from a given orientation plane (denoted as (xyz) for convenience). f = (p-p0) / (1-p0) (4) In equation (4), p0 is a value based on known powder X-ray diffraction data for the target substance, and p is a value based on the X-ray diffraction pattern of the target substance, and can be calculated by the following equations (5) and (6), respectively. p0=I0(xyz) / ΣI0(hkl) ···(5) p = I(xyz) / ΣI(hkl) (6) In formulas (5) and (6), h, k, and l are integers including 0. In formula (5), ΣI0(hkl) means the sum of the diffraction intensities (usually relative intensities with the greatest intensity taken as 100) of the peaks of all planes obtained from known powder X-ray diffraction data for the substance of interest, and I0(xyz) means the diffraction intensity (same as above) of the peak of a specified orientation plane (xyz) obtained from known powder X-ray diffraction data for the substance of interest.
[0023] In the XRD diffraction pattern of a substance having a face-centered cubic structure, the diffraction intensities of the three peaks belonging to the (111), (200) and (220) planes are prominent. Therefore, the present inventors simplified the definition of the Lotgering factor f, which requires the diffraction intensities of the peaks of all planes, and decided to determine a factor F similar to the Lotgering factor only from the diffraction intensities of the peaks of the (111), (200) and (220) planes. That is, the above formulas (1) to (3) for determining the factor F were determined by modifying the formulas (4) to (6) for determining the Lotgering factor f. The present inventors found that the value of F of the plating film 33, 43 determined from the formulas (1) to (3) is significant as an index for knowing the adhesion between the resin layer 32, 42 and the plating film 33, 43.
[0024] The value of F can be from -1 to 1, and the closer to 1, the higher the orientation of the (111) plane of the plating film 33, 43. As described above, in the present invention, the value of F of the plating film 33, 43 is 0.20 or more and 0.50 or less. If the value of F is less than 0.20, the adhesion between the resin layer 32, 42 and the plating film 33, 43 is insufficient. If the value of F exceeds 0.50, the adhesion between the resin layer 32, 42 and the plating film 33, 43 increases, but the plating film 33, 43 must be formed with high orientation, which imposes strict restrictions on the production conditions, resulting in increased manufacturing costs. The value of F is preferably 0.23 or more and 0.48 or less, and more preferably 0.25 or more and 0.45 or less.
[0025] The metal having a face-centered cubic structure constituting the plating films 33, 43 is preferably at least one selected from the group consisting of Ni, Au, Cu, Ag, Pt, Pd, and Al. The thickness of plating films 33, 43 need only be sufficient to protect end faces 21A, 22A of ceramic body 20A of electronic component 10A from the reflow atmosphere. For example, in the case of Ni plating films, the thickness is preferably 2 μm or more and 10 μm or less.
[0026] When the external electrodes 30, 40 further include second plating films 34, 44 covering the plating films 33, 43, the second plating films 34, 44 are preferably at least one type selected from the group consisting of Sn, Au, Cu, and Pd. The second plating films 34, 44 may have any thickness that allows the solder material to wet and spread during reflow. For example, in the case of a Sn plating film, the average thickness is preferably 0.5 μm or more and 5.0 μm or less.
[0027] The thicknesses of the plating films 33, 43 and the second plating films 34, 44 are measured by performing X-ray fluorescence analysis on samples with each plating film exposed on the outermost surface, and fitting the obtained X-ray intensity to a calibration curve. The calibration curve is obtained by performing X-ray fluorescence analysis on a standard sample with a known thickness, and plotting the relationship between the obtained X-ray intensity and the thickness using a regression equation. The thickness of the plating film on the standard sample with a known thickness is measured by the following method. A number of standard samples are prepared in which the plating film thickness is changed by intentionally changing the plating conditions, and the cross sections of the samples are polished and electron microscope or scanning ion microscope images of the cross sections are obtained to measure the thickness of the plating film on the standard sample.
[0028] The resin layers 32, 42 of the external electrodes 30, 40 function as stress absorbing layers that suppress the generation of cracks in the ceramic body 20A due to external impact, thermal stress, etc. The resin layers 32, 42 contain conductive powder and a resin material. The conductive powder dispersed in the resin material provides the resin layers 32, 42 with electrical conductivity.
[0029] The conductive powder contained in the resin layer 32, 42 is preferably a metal powder. In particular, it is preferably at least one metal powder selected from the group consisting of Ag, Au, Ni, Cu, Pt, Pd and Al. These metals have a face-centered cubic structure like the metals constituting the plating film 33, 43, so that the crystallographic matching between the metal powder exposed on the surface of the resin layer 32, 42 and the plating film 33, 43 formed on the surface of the resin layer 32, 42 is good. Therefore, it is expected to promote the oriented growth of the plating film 33, 43. It is also expected to have an effect of improving the adhesion between the plating film 33, 43 and the resin layer 32, 42.
[0030] The resin material contained in the resin layers 32 and 42 is preferably a thermosetting resin, an ultraviolet-curing resin, etc., and is particularly preferably a thermosetting resin with excellent heat resistance. Suitable examples of the thermosetting resin include epoxy resin, phenol resin, urethane resin, silicone resin, and polyimide resin, and epoxy resin is particularly preferable because of its excellent heat resistance, moisture resistance, and adhesion. The resin material may be used alone or in combination of two or more types. A curing agent may be included together with the thermosetting resin. When an epoxy resin is used as the base resin, a known compound such as a phenol-based, amine-based, acid anhydride-based, or imidazole-based compound may be used as the curing agent.
[0031] The present invention is particularly effective for small chip-type electronic components 10A. This is because in small chip-type electronic components 10A, the contact area between the resin layers 32, 42 and the plating films 33, 43 is small, making the adhesion between them particularly important. For example, the present invention is suitable for electronic components 10A having a length of 0.6 mm to 1.0 mm and a width of 0.3 mm to 0.5 mm (corresponding to sizes 0603 to 1005).
[0032] In addition to the above-mentioned positive temperature coefficient thermistor, the electronic component 10A suitable for application of the first embodiment includes chip-type ceramic electronic components such as negative temperature coefficient (or negative temperature coefficient, NTC) thermistors, varistors, and capacitors. In these electronic components, the material constituting the ceramic body 20A is selected according to the required characteristics.
[0033] A method for manufacturing the electronic component 10A according to the first embodiment will be described using a positive temperature coefficient thermistor having the structure shown in FIG.
[0034] (Preparation of ceramic body 20A) The ceramic body 20A is formed from, for example, BaTiO3, CaTiO3, SrTiO3, CaZrO3, (BaSr)TiO3, Ba(ZrTi)O3, (BiZn)Nb2O7, or the like.
[0035] In the production of the ceramic body 20A shown in FIG. 1, first, predetermined amounts of ceramic raw materials such as BaCO3, TiO2, PbO, SrCO3, CaCO3, etc., semiconductor-forming agents such as Sm2O3, Er2O3, etc., sintering aids such as SiO2, and property adjusters such as MnO2 are weighed out as raw materials for the ceramic body 20A. The weighed raw materials are charged into a ball mill together with grinding media such as partially stabilized zirconia (PSZ) (hereinafter also referred to as PSZ balls) and pure water, and wet mixed and ground. The resulting mixture is calcined at a predetermined temperature (for example, 1000 to 1200°C) to obtain a calcined powder.
[0036] The calcined powder is mixed with an organic binder, a dispersing agent, and pure water, and then dried to form granules. The granules are molded to obtain a green body. The green body is degreased and debindered, and then fired at a predetermined temperature (1200 to 1400°C) in a predetermined atmosphere to obtain the ceramic body 20A.
[0037] (Formation of Underlayers 31 and 41) As shown in FIG. 1, after the ceramic body 20A is produced, base layers 31, 41 may be formed to cover the end faces 21A, 22A of the ceramic body 20A. The underlayers 31 and 41 are made of a material that has ohmic properties with the ceramic body 20A, such as Ag, Zn, Cr, Ni, Cu, Ti, W, V, Au, or Al, or an oxide. The underlayers 31, 41 are formed by various thin film forming methods (such as sputtering and vapor deposition), various printing methods, dipping methods, etc. When formed by various printing methods or dipping methods, the underlayers 31, 41 are obtained by baking a conductive paste. The baking temperature of the conductive paste is, for example, 500 to 900°C.
[0038] (Formation of resin layers 32, 42) Resin layers 32, 42 containing conductive powder are formed on the ends of the ceramic body 20A. The resin layers 32, 42 are provided by hardening a resin electrode paste having fluidity. The resin electrode paste contains a conductive powder and a resin raw material. The resin electrode paste is applied to the ends of the ceramic body 20 so as to cover the base layers 31, 41, and then the resin raw material in the resin electrode paste is hardened.
[0039] The conductive powder contained in the resin electrode paste is the same as the conductive powder contained in the resin layers 32, 42 of the electronic component 10A. In other words, the conductive powder contained in the resin electrode paste is preferably a metal powder, and in particular, is preferably at least one type of metal powder selected from the group consisting of Ag, Au, Ni, Cu, Pt, Pd, and Al.
[0040] The resin raw material contained in the resin electrode paste is one that can form the resin material contained in the resin layers 32 and 42 of the electronic component 10A. In other words, the resin raw material contained in the resin electrode paste is preferably a resin raw material such as a thermosetting resin before curing or a UV-curable resin before curing, and is particularly preferably a resin raw material of a thermosetting resin with excellent heat resistance. As the resin raw material of a thermosetting resin, for example, a resin raw material such as an epoxy resin, a phenolic resin, a urethane resin, a silicone resin, or a polyimide resin is suitable, and is particularly preferably a resin raw material of an epoxy resin. The resin raw material is preferably a liquid resin raw material. The resin raw material may be used alone or in a mixture of two or more types. It is preferable to use a curing agent together with the resin raw material of a thermosetting resin. When an epoxy resin is used as the base resin, a known compound such as a phenolic, amine, acid anhydride, or imidazole compound can be used as a curing agent.
[0041] The amount of the conductive powder to be mixed is preferably 70 parts by weight or more and 90 parts by weight or less with respect to 10 parts by weight or more and 30 parts by weight or less of the resin material.
[0042] (Formation of plating films 33, 43) Plated films (first plated films) 33, 43 that are in direct contact with the resin layers 32, 42 are formed. The plating films 33 and 43 are made of a metal having a face-centered cubic structure. As described above, the metal having a face-centered cubic structure is preferably at least one selected from the group consisting of Ni, Au, Cu, Ag, Pt, Pd, and Al.
[0043] The plating films 33, 43 can be formed by a known plating method such as a method utilizing centrifugal force or an electrolytic barrel plating method. Any known plating bath can be used. When the metal having a face-centered cubic structure is Ni, for example, a matte nickel bath, a Watts bath, a sulfamic acid bath, a Woodstrike bath, a total chloride bath, etc. can be used. By appropriately controlling the plating conditions for the plating films 33, 43, it is possible to form the plating films 33, 43 having an F value, which is an index of orientation, of 0.20 or more and 0.50 or less.
[0044] (Formation of second plating films 34, 44) Second plating films 34, 44 may be formed to cover the plating films 33, 43. As described above, the second plating films 34, 44 are preferably made of at least one type selected from the group consisting of Sn, Au, Cu, and Pd. The second plating films 34, 44 are formed by a known plating method such as a method using centrifugal force or an electrolytic barrel plating method. Known plating baths can be used, and for example, in the case of Sn plating films, acid baths and alkaline baths can be used. As acid baths, sulfuric acid baths, methanesulfonic acid baths, etc. can be used.
[0045] While the method for manufacturing electronic component 10A according to embodiment 1 of the present invention has been described above using a positive temperature coefficient thermistor as an example, other electronic components can also be manufactured as appropriate based on the description in this specification.
[0046] [Embodiment 2] The electronic component according to embodiment 2 differs from embodiment 1 in that an internal electrode is provided inside the ceramic body, but other configurations are similar to those of embodiment 1. The electronic component according to embodiment 2 will be described, focusing on the differences from embodiment 1.
[0047] 2 is a schematic cross-sectional view of an electronic component 10B according to a second embodiment of the present invention. The electronic component 10B shown in FIG. The electronic component 10B includes a ceramic body 20B and external electrodes provided on ends of the ceramic body 20B. In the second embodiment, the electronic component 10B further includes internal electrodes 71, 72 inside the ceramic body 20B. The configuration of the external electrodes is the same as in the first embodiment, and therefore a description thereof will be omitted.
[0048] The ceramic body 20B is composed of multiple ceramic layers 200. The multiple ceramic layers 200 and internal electrodes 71, 72 are alternately stacked to form a laminate 80. The internal electrode 71 is exposed from one end face 21B of the ceramic body 20B, and the internal electrode 72 is exposed from the other end face 22B of the ceramic body 20B. The base layers 31, 41 of the external electrodes 30, 40 formed on the ends of the ceramic body 20B are in contact with the internal electrodes 71, 72 exposed from the end faces 21B, 22B of the ceramic body 20B.
[0049] In addition to the above-mentioned positive temperature coefficient thermistor, electronic components 10B suitable for application of embodiment 2 include chip-type ceramic electronic components with negative temperature coefficient (or negative temperature coefficient, NTC) thermistors, varistors, capacitors, etc., which have internal electrodes.
[0050] A method for manufacturing an electronic component 10B according to the second embodiment will be described using a positive temperature coefficient thermistor having internal electrodes 71 and 72 as shown in FIG.
[0051] (Preparation of ceramic body 20B) To produce the ceramic body 20B, first, calcined powder of raw materials is produced in the same manner as in the ceramic body 20A of the first embodiment, and then the laminate 80 is produced using the calcined powder.
[0052] The ceramic body 20B is formed from, for example, BaTiO3, CaTiO3, SrTiO3, CaZrO3, (BaSr)TiO3, Ba(ZrTi)O3, (BiZn)Nb2O7, or the like. The material forming the internal electrodes 71, 72 is not particularly limited as long as it is conductive, and examples thereof include Ag, Cu, Pt, Ni, Al, Pd, and Au, with Ag, Cu, and Ni being particularly preferred.
[0053] First, as the raw materials of the ceramic body 20B, ceramic raw materials such as BaCO3, TiO2, PbO, SrCO3, CaCO3, etc., semiconductor-forming agents such as Sm2O3, Er2O3, etc., sintering aids such as SiO2, and property adjusters such as MnO2 are weighed out in predetermined amounts. The weighed raw materials are put into a ball mill together with grinding media such as partially stabilized zirconia (PSZ) (hereinafter also referred to as PSZ balls) and pure water, and wet mixed and ground. The obtained mixture is calcined at a predetermined temperature (for example, 1000 to 1200°C) to obtain a calcined powder.
[0054] The obtained calcined powder is added with an organic binder, and the mixture is mixed in a wet manner to form a slurry. The mixture is then molded using a doctor blade method or the like to produce a ceramic green sheet of a desired thickness. Next, a conductive paste for internal electrodes is applied to the surface of the ceramic green sheet to form an internal electrode pattern. The conductive paste for internal electrodes can be prepared, for example, by dispersing a metal powder and an organic binder in an organic solvent. The paste for internal electrodes may be applied, for example, by screen printing or the like. A predetermined number of ceramic green sheets on which the internal electrode patterns are thus formed are stacked, and then the top and bottom are sandwiched and pressed with ceramic green sheets on which the internal electrode patterns are not formed to produce a laminate. After cutting the laminate to a predetermined size, the laminate is subjected to a degreasing process and a debindering process, and then fired at a predetermined temperature (1200 to 1400°C) and in a predetermined atmosphere to obtain a laminate 80 having a laminate structure consisting of the ceramic body 20B (a plurality of ceramic layers 200) and the internal electrodes 71 and 72.
[0055] (Formation of Underlayers 31 and 41) 2, after fabrication of the ceramic body 20B, base layers 31, 41 may be formed to cover end faces 21B, 22B (end faces of the laminate 80) of the ceramic body 20B. The base layers 31, 41 are electrically connected to the internal electrodes 71, 72 exposed from the end faces 21B, 22B of the ceramic body 20B. The method for forming the underlayers 31 and 41 is the same as in the first embodiment, and therefore the description will be omitted.
[0056] (Formation of resin layers 32, 42) Resin layers 32, 42 containing conductive powder are formed on the ends of the ceramic body 20B. The method for forming the resin layers 32, 42 is the same as in the first embodiment, and therefore a description thereof will be omitted.
[0057] (Formation of plating films 33, 43) Plated films (first plated films) 33, 43 are formed so as to be in direct contact with the resin layers 32, 42. The method for forming the plated films 33, 43 is the same as in the first embodiment, and therefore a description thereof will be omitted.
[0058] (Formation of second plating films 34, 44) Second plating films 34, 44 may be formed to cover the plating films 33, 43. The method for forming the second plating films 34, 44 is the same as in the first embodiment, and therefore the description thereof will be omitted.
[0059] The above describes the manufacturing method of electronic component 10B according to embodiment 2 of the present invention using a positive temperature coefficient thermistor having internal electrodes as an example. However, other electronic components having internal electrodes can also be manufactured as appropriate based on the description in this specification. EXAMPLES
[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to such examples.
[0061] [Example 1] (Preparation of the object to be plated) A "substrate to be plated" for forming a plating film was prepared. A barium titanate-based semiconductor (hereafter referred to as "element") measuring 0.53 mm (L) x 0.27 (W) x 0.27 (T) was prepared. An underlayer was formed by sputtering on the WT surface of the element to obtain an ohmic junction with the element. The underlayer had a thickness of 2.5 μm. Next, a resin layer made of epoxy resin and silver powder was formed on the WT surface so as to cover the underlayer. In this way, a "plated object" was obtained that included the element, underlayer, and resin layer.
[0062] (Preparation of plating film and second plating film) A nickel plating film was formed on the surface of the resin layer of the plated object by electrolytic barrel plating. A Watts bath (pH 4.5, bath temperature 55°C, nickel sulfate 240-300g / L, nickel chloride 45-50g / L, boric acid 30-40g / L) was used as the plating bath. Metallic nickel was contacted with the anode electrode as the nickel source.
[0063] In barrel plating, metallic media (conductive media) were used to assist electrical conduction between the objects to be plated, and insulating resin balls were used to stir the contents of the barrel. First, the object to be plated and the conductive medium were placed inside the barrel container. The cathode electrode was placed in a position inside the barrel container where it contacted the object to be plated and the conductive medium. Furthermore, a resin ball for stirring was placed inside the barrel container. Thereafter, a current was passed between the anode and the cathode at a predetermined current density for a predetermined time while rotating and swinging the barrel, thereby forming a nickel plating film of a desired thickness on the surface of the resin layer of the object to be plated. In Example 1, the average thickness of the nickel plating film was 6.74 μm.
[0064] Furthermore, a tin plating film (second plating film) was formed on the surface of the nickel plating film by electrolytic barrel plating. There are acidic and alkaline baths for plating baths, but an acidic bath was selected. As the acidic bath, a sulfuric acid bath or a methanesulfonic acid bath was used. In addition, metal tin was brought into contact with the anode electrode as a tin source. Other plating conditions were the same as those for the formation of the nickel plating film. In Example 1, the average thickness of the tin plating film was 4.37 μm.
[0065] After the formation of the tin plating film, the element was washed with pure water and dried in a thermostatic chamber at 85° C. for 20 minutes and then at 120° C. for 6 hours to prepare a plated sample (measurement sample).
[0066] (Evaluation of the orientation of nickel plating film) In order to measure the orientation of the nickel plating film, the tin plating film of the measurement sample was dissolved and removed with a solvent. The solvent is not particularly limited as long as it can selectively dissolve tin, but in Example 1, a solvent mainly composed of boron fluoride was used. For the measurement sample after removing the tin plating film, the exposed nickel plating film was subjected to micro-X-ray diffraction measurement using a D8 DISCOVER manufactured by BRUKER axs. The two-dimensional X-ray diffraction image obtained using a two-dimensional detector was converted into a one-dimensional profile. The diffraction intensity areas of the XRD diffraction peaks of the (111) plane, (200) plane, and (220) plane of the nickel plating film, I(111), I(200), and I(220), were used as the diffraction intensity area values of the peaks of the obtained one-dimensional profile. The diffraction intensity values were calculated as relative intensities with the largest intensity I(111) being taken as 100.
[0067] F, which is an index showing the orientation of the (111) plane, was calculated using the following formulas (1) to (3). The value of F for the nickel plating film of Example 1 was 47.7% (0.477).
[0068] F = (P - P0) / (1 - P0) (1) In formula (1), P0 and P were calculated by the following formulas (2) and (3). P0=I0(111) / {I0(111)+I0(200)+I0(220)}...(2) P=I(111) / {I(111)+I(200)+I(220)}...(3) In equation (2), I0(111), I0(200), and I0(220) are the diffraction intensities of the (111), (200), and (220) planes, respectively, obtained from the powder X-ray diffraction data of nickel obtained from the ICDD database. In equation (3), I(111), I(200), and I(220) are the diffraction intensities of the (111), (200), and (220) planes obtained from XRD diffraction measurement of the nickel plating film of the measurement sample.
[0069] In addition, using formulas (1-2), (2-2) and (3-2), F, which indicates the orientation of the (200) plane, (200) was calculated and is shown in Table 1. F (200) =(P (200) -P 0(200) ) / (1-P 0(200) ) · · · (1-2) In formula (1-2), P 0(200) and P (200) was calculated using the following formulas (2-2) and (3-2). P 0(200) =I0(200) / {I0(111)+I0(200)+I0(220)}···(2-2) P (200) =I(200) / {I(111)+I(200)+I(220)}···(3-2) In the formulas (2-2) and (3-2), I0(111), I0(200), I0(220), I(111), I(200), and I(220) are defined as in the formulas (2) and (3).
[0070] Furthermore, using formulas (1-3), (2-3) and (3-3), F, which shows the orientation of the (220) plane, (220) was calculated and is shown in Table 1. F (220) =(P (220) -P 0(220) ) / (1-P 0(220) ) · · · (1-3) In formula (1-3), P 0(220) and P (220) was calculated using the following equations (2-3) and (3-3). P 0(220) =I0(220) / {I0(111)+I0(200)+I0(220)}···(2-3) P (220) =I(220) / {I(111)+I(200)+I(220)}···(3-3) In the formulas (2-3) and (3-3), I0(111), I0(200), I0(220), I(111), I(200) and I(220) are defined as in the formulas (2) and (3).
[0071] (Evaluation of adhesion) The adhesion between the nickel plating film and the resin layer was evaluated by the fracture strength obtained by the lateral shear strength test method and the peeling mode at the time of fracture. The plated sample (measurement sample) was mounted on a copper-clad laminated glass cloth-based epoxy resin substrate (JIS C 6484:2005). First, Sn-3Ag-0.5Cu solder paste was screen-printed on the substrate to a thickness of 200 μm. The measurement sample was placed on the solder paste on the substrate with the WT side (the side on which the plating film was formed) facing the substrate, and reflow-mounted by passing it through a reflow furnace with a nitrogen gas atmosphere at a maximum temperature of 220°C at room temperature.
[0072] To measure the adhesion strength, a mounted test sample was pushed sideways with a push-pull gauge, and the strength at which the test sample peeled off from the substrate was measured, similar to JIS 62137-1-2:2010. In addition, after the measurement sample was peeled off from the board, the solder part of the board (the part where the measurement sample was mounted) was observed using a digital microscope and a scanning electron microscope to determine whether the mode of peeling was due to ceramic destruction (the element was destroyed and peeled off) or electrode destruction (the interface between the nickel plating film and the resin electrode was destroyed and peeled off, or the nickel plating film itself was destroyed and peeled off).
[0073] Using 10 measurement samples, adhesion strength measurements and peeling mode observations were performed 10 times each. The average fracture strength was 7.95 N, and the number of ceramic fractures and electrode fractures in the peeling modes were 10 and 0, respectively.
[0074] [Example 2] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to 35.7% (0.357), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 5.32 μm and 3.16 μm, respectively. The average fracture strength of the 10 pieces was 6.85 N, and the peeling modes were 10 for ceramic fracture and 0 for electrode fracture, respectively.
[0075] [Example 3] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to 25.8% (0.258), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 7.02 μm and 3.20 μm, respectively. The average fracture strength of the 10 pieces was 7.43 N, and the peeling modes were 10 for ceramic fracture and 0 for electrode fracture, respectively.
[0076] [Comparative Example 1] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to 1.96% (0.0196), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 6.21 μm and 3.57 μm, respectively. The average fracture strength of the 10 pieces was 4.53 N, and the peeling modes were 3 for ceramic fracture and 7 for electrode fracture, respectively.
[0077] [Comparative Example 2] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to 5.02% (0.0502), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 5.78 μm and 3.34 μm, respectively. The average fracture strength of the 10 pieces was 3.97 N, and the peeling modes were 3 for ceramic fracture and 7 for electrode fracture, respectively.
[0078] [Comparative Example 3] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to -1.16% (-0.0116), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 5.19 μm and 3.37 μm, respectively. The average fracture strength of the 10 pieces was 5.04 N, and the peeling modes were 2 for ceramic fracture and 8 for electrode fracture, respectively.
[0079] [Comparative Example 4] Except for changing the plating conditions of the nickel plating film to set the F value of the nickel plating film to -10.9% (-0.109), a plated sample (measurement sample) was prepared in the same manner as in Example 1, and the adhesion strength was evaluated. The average thicknesses of the nickel plating film and the tin plating film were 5.54 μm and 3.22 μm, respectively. The average fracture strength of the 10 pieces was 4.67 N, and the peeling modes were 3 for ceramic fracture and 7 for electrode fracture, respectively.
[0080] Table 1 summarizes the results of Examples 1 to 3 and Comparative Examples 1 to 4. Plated samples (measurement samples) with an F value indicating the orientation of the (111) of the nickel plating film of 20.0% or more and 50.0% or less (0.20 or more and 0.50 or less) had high fracture strength after solder mounting, and in the evaluation of the peeling mode, no samples showed electrode destruction (the interface between the nickel plating film and the resin electrode was destroyed and peeled off, or the nickel plating film itself was destroyed and peeled off). In other words, it was confirmed that peeling of the nickel plating film was suppressed and the adhesive strength between the nickel plating film and the resin layer was improved by improving the orientation of the (111) of the nickel plating film so that the F value was 0.20 or more and 0.50 or less.
[0081] [Table 1]
[0082] This application claims priority to Patent Application No. 2021-141837, filed in Japan on August 31, 2021, the entire contents of which are incorporated herein by reference. [Explanation of symbols]
[0083] 10. Electronic Components 20 Ceramic body 200 ceramic layers 21, 22 End faces of ceramic body 30, 40 external electrode 31, 41 Base layer 32, 42 Resin layer 33, 43 Plating film 34, 44 Second plating film 71, 72 Internal electrode 80 Laminate
Claims
1. An electronic component comprising a ceramic body and external electrodes on ends of the ceramic body, the external electrode includes a resin layer containing a conductive powder and a plating film on and in direct contact with the resin layer, The plating film is made of a metal having a face-centered cubic structure, The electronic component has a plating film having a value of F of 0.20 or more and 0.50 or less, as calculated by the following formula (1): F=(P-P 0 ) / (1-P 0 )・・・(1) In formula (1), P 0 and P are calculated by the following equations (2) and (3). P 0 =I 0 (111) / {I 0 (111)+I 0 (200)+I 0 (220)}・・・(2) P=I(111) / {I(111)+I(200)+I(220)}...(3) In formula (2), I 0 (111), I 0 (200) and I 0 (220) are the diffraction intensities of the (111) plane, the (200) plane, and the (220) plane, respectively, obtained from known powder X-ray diffraction data for the metals constituting the plating film, In formula (3), I(111), I(200) and I(220) are the diffraction intensities of the (111), (200) and (220) planes, respectively, obtained from the X-ray diffraction pattern of the plating film.
2. 2. The electronic component according to claim 1, wherein the metal having a face-centered cubic structure is at least one selected from the group consisting of Ni, Au, Cu, Ag, Pt, Pd, and Al.
3. The electronic component according to claim 1 or 2, wherein the conductive powder is a metal powder.
4. The electronic component according to claim 1 , wherein the resin layer contains a thermosetting resin.
5. The electronic component according to claim 1 , wherein the external electrodes further include a second plating film covering the plating film.
6. 3. The electronic component according to claim 1, wherein the electronic component has a length of 0.6 mm or more and 1.0 mm or less and a width of 0.3 mm or more and 0.5 mm or less.
Citation Information
Patent Citations
Laminated ceramic capacitor
JP1999162771A
Chip-type electronic component and its manufacturing method
JP2004119798A
Ceramic electronic component
JP2013110363A
Manufacturing method of electronic component contact member and electronic component contact member
JP2017197788A